A practical CFD modeling approach to estimate outlet boundary conditions of industrial multistage spray dryers: Inert particle flow field investigation. Issue 7 (19th May 2019) - Afshar, Sepideh; Metzger, Lloyd; Patel, Hasmukh; Selomulya, Cordelia; Woo, Meng Wai
Abstract: Industrial multistage spray drying systems often have limited in situ process measurements to provide sufficient information for computational fluid dynamics (CFD) simulations of the primary drying chamber. In this case study on the spray dryer at Davis Dairy Plant (South Dakota State University), uncertainties were encountered in specifying the outlet boundary conditions of the spray drying chamber with two outlets: the side outlet and the bottom outlet leading to the second stage external vibrating bed. Using the available data on the vacuum pressure of the chamber, a numerical framework was introduced to approximate suitable outlet boundary conditions for the drying chamber. The procedure involved analyzing the ratio of the airflow rate between the two outlets and using a pseudo-tracer inert particle injection analysis. The goal of this approach was to determine a suitable range of outlet vacuum pressure that will lead to realistic particle movement behaviors during the actual plant operation. The protocol developed here will be a useful tool for CFD modeling of large scale multistage spray drying systems. Abbreviations: ARC: Australian Research Council; CFD: Computational Fluid Dynamics; FFT: Fast Fourier Transform; MCC: Micellar Casein Concentrate; PRESTO: Pressure Staggering Option; SDSU: South Dakota State University; SIMPLE: Semi − Impilicit Method for Pressure Linked Equations; WPC: Whey Protein Concentrate